Sintesis dan Karakteristik Membran Komposit Akrilonitril Butadiena Stirena (ABS)-Kitosan Tersulfonasi untuk Direct Metanol Fuel Cell (DMFC) - Hidayati, Nur; Mujiburohman, Muhammad; Abdillah, Hamid; Harmoko, Tri; Arimurti, Rizki Dyah (Jurnal Matematika dan Sains, 2017)
Direct Methanol Fuel Cell (DMFC) is a type of fuel cell that converts methanol directly into electrical energy. The commercialization constraints of fuel cells in Indonesia is due to the high cost of manufacturing, including the expensive electrolyte membrane which is one of the important components of fuel cells. Utilization of cheap and abundant local materials such as acrylonitrile butadiene styrene (ABS) and chitosan can reduce the fuel cell manufacturing cost burden. The membrane currently used for DMFC is the Nafion® membrane. The superiority of Nafion® membrane has high ionic conductivity and membrane stability, while Nafion® membrane deficiency is a very expensive price and has a high enough methanol permeability that can lead to a decrease in overall cell voltage performance. This study studied the characteristics of ABS-sulfonated Chitosan membrane membrane with ratio (20:80) and (40:60) prepared on 6-hour, 12 hour, 18 hour, 24 hour sulphonation time variation. The experimental results show a sulfonation time of 24 hours, in the ratio of ABS: Chitosan (20:80 wt) provides membrane characteristics such as water uptake 48.50%, swelling degree 25%, ion exchange chamber 2.030 meq / g, and methanol permeability 2,9336x10 -6 cm2 / s.